FE-MG ORDER-DISORDER IN ORTHOPYROXENES - Wang L.; Moon N.; Zhang Y.; Dunham W.R.; Essene E.J. (My University, 2005)
Published data on the distribution of Fe and Mg between the two distinct octahedral sites (M1 and M2) in orthopyroxenes show that the equilibrium Fe-Mg distribution coefficient (KD) is roughly constant at intermediate ferrosilite content (XFs of 0.2 to 0.6) but at low XFs (<0.2) is either anomalously high (Mössbauer data) or low (XRD data) compared to KD at intermediate XFs. We report an experimental study on the equilibrium KD values for two natural single crystals of orthopyroxene (with XFs of 0.011 and 0.160) using a high-sensitivity Mössbauer spectrometer. The KD values were determined at 1 bar and temperatures between 600 and 1000°C, and reversed at 600 to 900°C. The values are found to be independent of orthopyroxene composition at a given temperature within analytical uncertainties, and in agreement with KD values at intermediate XFs. A least-squares fit to the KD data yields: lnKD = 0.391(±0.131) − 2205(±141)/T, where T is temperature in K, and uncertainties are at the 2σ level. This equation is valid for XFs values up to at least 0.6. We suggest that previous Mössbauer and XRD data at low XFs were compromised by analytical difficulties. The new result that KD is roughly independent of XFs greatly simplifies treatment of equilibrium and speedometry based on Fe-Mg order-disorder in orthopyroxene.